Caesalpinia pulcherrima lowered serum carcinoembryonic antigen and antigen 125 in 7,12-Dimethylbenz[a]anthracene-induced Mammary Carcinogenesis in Female Albino Rats - Abraham Ehinomhen Ubhenin; Adedotun A. Adefolalu; Kelly Oriakhi; Fatima Adis Adamude; Emeka John Dingwoke; Joshua Onyeka Ikebuiro; Benjamin Comfort Chiwendu; Mabruqah Liman Muhammad; Kingsley Omage (Heliyon, 2024)
Aim: This study is aimed at evaluating the anticancer effect of the aqueous extract of Caesalpinia pulcherrima (L.) Sw in 7,12-Dimethlbenz[a]anthracene (DMBA) – induced mammary cancer. Methods: Tumors were induced via a single intraperitoneal injection of DMBA (dissolved in olive oil) at a dose of 80 mg/kg body weight to the test rats and allowed to develop for about four months. They were treated with cyclophosphamide and an aqueous extract of Caesalpinia pulcherrima at doses of 10 and 250 mg/kg body weight, respectively, for 28 days. Serum levels of cancer antigen 125 (CA125), carcinoembryonic antigen (CEA) activity, cyclooxygenase-2 (COX-2), and cytochrome p450 oxidase (cytp450) activity, as well as other diagnostic enzymes, were estimated. Results: The result revealed that DMBA is associated with a significant (p < 0.05) increase in the serum levels of CA125, CEA, COX-2, cytp450, lactate dehydrogenase (LDH), alkaline phosphatase (ALP), aspartate aminotransferase (AST), and alanine aminotransferase (ALT) of the rats, thus suggesting tumor-promoting and hepatotoxic effects of DMBA. There was also a significant (p < 0.05) reduction of serum levels of these cancer and liver biomarker enzymes in the groups treated with cyclophosphamide and Caesalpinia pulcherrima compared to the untreated group, thus suggesting anticancer activity of Caesalpinia pulcherrima. The anticancer effect of Caesalpinia pulcherrima was further confirmed by the disappearance of infiltrative fibrous cells and the absence of inflammatory cells from the photomicrographs of the rats treated with Caesalpinia pulcherrima. Conclusion: Our findings show that Caesalpinia pulcherrima possesses anticancer activity, and could protect against mammary cancer.